Estimation of Concentration of K-40 by Gamma Spectroscopy and Atomic Emission Spectroscopy in the Environmental Samples of Northern Kathmandu Valley - Yadav, P. N.; Rajbhandari, P.; Shrestha, K. K. (Journal of Nepal Chemical Society, 2013)
The concentration of K-40 was estimated by atomic emission spectroscopy (AES) and specific activity by gamma ray spectroscopy using by means of a multichannel analyzer (MCA) in the soil and water samples of northern parts of the Kathmandu valley. AES method was found to be sensitive and rapid for the routine analysis of water samples, however, cannot implement for the analysis of soil samples due to the loss of significant amount of potassium during the extraction process. The specific activity determined by a MCA in water samples ranged from 2.25 Bq/Kg to 17.87 Bq/Kg and for soil samples, from 17.48 Bq/Kg to 412.26 Bq/Kg. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9255 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 75-80 Uploaded date: 12/5/2013